ANALISIS KUALITAS AIR SUNGAI DI SEKITAR PT MERTEX MOJOKERTO BERDASARKAN PARAMETER FISIKA, KIMIA, DAN LOGAM BERAT - Orisia Toriqotul Ulum; Manda Eka Dayinia; Nur Ainun; Shinta Dian Pramesty; Rusmini (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
Rivers are vital water resources that support ecosystems, yet industrial activities may reduce water quality through organic, nutrient, and heavy metal pollution. This study aims to analyze the water quality of rivers surrounding PT Mertex Mojokerto by measuring pH, TDS, DO, ammonia (NH₄⁺), nitrate (NO₃⁻), and heavy metal concentrations, and comparing the results with Indonesian water quality standards (Government Regulation No. 22/2021 and Ministry of Health Regulation No. 32/2017). Water samples were collected and analyzed using a pH meter, TDS meter, DO test kit, and specific test kits for heavy metals, ammonia, and nitrate. The results showed that pH (7.4–7.6), TDS (156 ppm), and DO (7.5 ppm) were within acceptable limits. Ammonia was not detected (0 ppm), while nitrate reached 50 ppm, exceeding the permissible limit (10 ppm). Most hazardous heavy metals were not detected, but zinc (Zn) was recorded at 5 mg/L, far above the maximum allowable concentration of 0.05 mg/L. Overall, the river water quality near PT Mertex is relatively good, although high levels of nitrate and zinc indicate potential pollution that could threaten aquatic ecosystem balance.